Decay of References to Web sites in Articles Published in General Medical Journals: Mainstream vs Small Journals - Habibzadeh, P. (Schattauer, 2013)
BACKGROUND: Over the last decade, Web sites (URLs) have been increasingly cited in scientific articles. However, the contents of the page of interest may change over the time. OBJECTIVE: To investigate the trend of citation to URLs in five general medical journals since January 2006 to June 2013 and to compare the trends in mainstream journals with small journals. METHODS: References of all original articles and review articles published between January 2006 and June 2013 in three regional journals – Archives of Iranian Medicine (AIM), Eastern Mediterranean Health Journal (EMHJ), and Journal of Postgraduate Medical Institute (JPMI) – and two mainstream journals – The Lancet and British Medical Journal (BMJ) – were reviewed. The references were checked to determine the frequency of citation to URLs as well as the rate of accessibility of the URLs cited. RESULTS: A total of 2822 articles was studied. Since January 2006 onward, the number of citations to URLs increased in the journals (doubling time ranged from 4.2 years in EMHJ to 13.9 years in AIM). Overall, the percentage of articles citing at least one URL has increased from 24% in 2006 to 48.5% in 2013. Accessibility to URLs decayed as the references got old (half life ranged from 2.2 years in EMHJ to 5.3 years in BMJ). The ratio of citation to URLs in the studied mainstream journals, as well as the ratio of URLs accessible were significantly (p<0.001) higher than the small medical journals. CONCLUSION: URLs are increasingly cited, but their contents decay with time. The trend of citing and decaying URLs are different in mainstream journals compared to small medical journals. Decay of URL contents would jeopardize the accuracy of the references and thus, the body of evidence. One way to tackle this important obstacle is to archive URLs permanently.